Paradoxical redistribution of pulmonary blood flow in prone and supine humans exposed to hypergravity - Petersson, Johan; Rohdin, Malin; Sanchez-Crespo, Alejandro; Nyren, Sven; Jacobsson, Hans; Larsson, Stig A; Lindahl, Sten G. E; Linnarsson, Dag; Glenny, Robb W; Mure, Margareta (Journal of applied physiology (1985), 2006)
1 Department of Anesthesiology and Intensive Care, Karolinska University Hospital Solna; 2 Section of Environmental Physiology, Department of Physiology and Pharmacology, Karolinska Institutet; 3 Section of Nuclear Medicine, Department of Hospital Physics, Karolinska University Hospital Solna; 4 Medical Radiation Physics, Department of Oncology-Pathology, Stockholm University and Karolinska Institutet; 5 Department of Radiology, Karolinska University Hospital Solna, Stockholm, Sweden; and 6 Departments of Medicine and Physiology and Biophysics, University of Washington, Seattle, Washington Submitted 30 December 2004 ; accepted in final form 2 September 2005 We hypothesized that exposure to hypergravity in the supine and prone postures causes a redistribution of pulmonary blood flow to dependent lung regions. Four normal subjects were exposed to hypergravity by use of a human centrifuge. Regional lung perfusion was estimated by single-photon-emission computed tomography (SPECT) after administration of 99m Tc-labeled albumin macroaggregates during normal and three times normal gravity conditions in the supine and prone postures. All images were obtained during normal gravity. Exposure to hypergravity caused a redistribution of blood flow from dependent to nondependent lung regions in all subjects in both postures. We speculate that this unexpected and paradoxical redistribution is a consequence of airway closure in dependent lung regions causing alveolar hypoxia and hypoxic vasoconstriction. Alternatively, increased vascular resistance in dependent lung regions is caused by distortion of lung parenchyma. The redistribution of blood flow is likely to attenuate rather than contribute to the arterial desaturation caused by hypergravity. single-photon-emission computed tomography; regional lung perfusion Address for reprint requests and other correspondence: J. Petersson, Dept. of Anesthesiology and Intensive Care, Karolinska Univ. Hospital, Solna, 171 76 Stockholm, Sweden (e-mail: johan.peterssonatkarolinska.se )